Produksi Benih dan Polong Segar Buncis (Phaseolus vulgaris L.) yang Dipanen dari Pertanaman Tumpangsari dengan Sorgum (Sorghum bicolor [L.] Moench) dan Monokultur - Pramono, Eko; Kurnianti, Vidia Dwi; Utomo, Setyo Dwi; Ginting, Yohannes Cahya (JURNAL AGROTROPIKA, 2023)
Bean (Phaseolus vulgaris L.) is generally cultivated in monoculture (sole cropping) by farmers in the highlands as main crops. Increasing land use efficiency (LUE) by inter-cropping sorghum on bean requires certain cultivation techniques so as not reducing the production of seeds or fresh fruit bean. This experiment aimed at determine 1) the yields of seeds and fresh pods harvested from the bean-sorghum intercropping compared to those from the sole cropping and 2) the LUE of the bean-sorghum intercropping.  The research, which was conducted during April-September 2021 in Sekincau District, West Lampung Regency, Lampung Province, Indonesia used dwarf beans Balitsa-2 variety and climbing bean Horti-3 variety, each of which to be intercropped with sorghum of Numbu variety. Five levels of cropping system treatment were arranged in a Completely Randomized Block Design (CRBD) with six groups as six replications. The results showed that there was no difference the seeds yield and fresh pods of bean between those harvested from bean-sorghum intercropping and from monocultures. The seed yield harvested from the dwarf bean-sorghum intercropping was higher, whereas those harvested from the climbing bean-sorghum intercropping was lower, respectively, compared to those harvested from the monoculture. In producing fresh pods, intercroppings of dwarf bean-sorghum and climbing bean-sorghum increased the LUE, respectively. Whereas in producing seeds, the dwarf bean-sorghum intercropping increased the LUE, but the climbing bean-sorghum intercropping decreased the LUE. Key words : bean, fresh pods, intercropping, seeds, sorghum